Gut microbiota and meat quality - Chen, Binlong; Li, Diyan; Leng, Dong; Kui, Hua; Bai, Xue; Wang, Tao (Frontiers in Microbiology, 2022)
Sustainable meat production is important to providing safe and quality protein sources for humans worldwide. Intensive artiﬁcial selection and high energy input into the diet of many commercial animals for the last decade has signiﬁcantly increased the daily gain of body weight and shortened the raising period, but unexpectedly decreased the meat quality. The gastrointestinal tract of animals harbors a diverse and complex microbial community that plays a vital role in the digestion and absorption of nutrients, immune system development, pathogen exclusion, and meat quality. Fatty acid composition and oxidative stress in adipose and muscle tissue influences meat quality in livestock and poultry. Recent studies showed that nutraceuticals are receiving increased attention, which could alter the intestinal microbiota and regulate the fat deposition and immunity of hosts to improve their meat quality. Understanding the microbiota composition, the functions of key bacteria, and the host-microbiota interaction is crucial for the development of knowledge-based strategies to improve both animal meat quality and host health. This paper reviews the microorganisms that affect the meat quality of livestock and poultry. A greater understanding of microbial changes that accompany beneﬁcial dietary changes will lead to novel strategies to improve livestock and poultry meat product quality.